If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3n + 6n = 3 + -9 Combine like terms: 3n + 6n = 9n 9n = 3 + -9 Combine like terms: 3 + -9 = -6 9n = -6 Solving 9n = -6 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Divide each side by '9'. n = -0.6666666667 Simplifying n = -0.6666666667
| .6a-.75b=c | | 7(-2x+6)=126 | | 5a^2+20a+3=0 | | -3q+4=q | | 3(3x+4)+3(3x+4)=18x+30 | | 7x+4+4x+9=10x+3 | | 3(x+7)-3(x+2)=36 | | 6y^2+9y=11y-4 | | 4v^2-28v+49=0 | | 3(x+7)-3(x+2)=-36 | | 6+8(x-9)=9-3(x-9) | | z-5=7z-9-z | | x-6=7x | | x=5my-7b | | 8x+3-7x=11 | | 16w^2+27=0 | | 36x^2+12x+64=0 | | 12=8n-1 | | 3w-11w=48 | | 6=4x-9y | | 5(1.2k+6)=7.1+34.4 | | -7(6x+1)=-133 | | (9x^2)-252x+330=0 | | x-4x+3=-30 | | -3(3n-8)=30 | | p=-3*4+1 | | 3.2/16= | | (3x-4w)(5x-8w)= | | 8-4x=9-5x | | p=-3q+1 | | -3(4-3y)=3y+6 | | 2(6x+8)-5=12x+11 |